Historical review of the fiscal system (Financial Reform Association, 1884)
Contains section VI(2nd part)-IX(1st part), continued from tract no. 25, to be continued in tract no. 27. - Orig. publ. in different tract no. - Issued 1850 by the Liverpool Financial Reform Association. - Authorship claimed by Alexander Somerville. - Repr. - In pamphlet volume with title on spine: Financial reform tracts : 1848-51.